Political implications of the activities of TNCs: Current trends and impact on the concepts of power, legitimacy and sovereignty - S. Yu. Zaitsev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Amidst dramatic transformation of international relations, both traditional and new actors are undergoing major changes. The multinational corporations (MNCs), which have dramatically strengthened their positions in the world economy and politics since the middle of the 20th century due to favorable economic environment, as well as their ability to quickly convert considerable material, financial, intellectual and institutional resources into political clout, are no exception. All this points to the need to address MNCs as full-fledged political entities and examine their impact on traditional actors in a changing international context. The first section examines various approaches to conceptualization of the evolution of MNCs as actors of world politics. It also identifies the specifics of their position within the framework of the contemporary international relations system. The author focuses on such trends as digitalization, growing influence of companies with a platform business model, increasing engagement of corporations in addressing global issues, scaling up investments in the host countries’ infrastructure through new formats of public-private partnership, as well as growth in the number of state-owned TNCs. The second section examines the activities of TNCs as political actors in contemporary international relations from two angles. On the one hand, it considers the TNCs’ operations in terms of power, legitimacy and sovereignty that is how these categories manifest themselves in the activities of corporations and their interactions with other actors and society. On the other hand, it poses the question about how various trends in the development of TNCs, in turn, affect the content and essence of these categories. The author concludes that cooperation with TNCs offers national states new economic, social and political opportunities. At the same time, corporations are becoming increasingly autonomous, which can have a serious impact on conventional ideas of power, legitimacy and sovereignty, up to the erosion of the state monopoly on legitimate violence. The latter may have a serious impact on conventional ideas of power, legitimacy and sovereignty, up to the erosion of the state monopoly on legitimate violence. There is thus a pressing need to further study various types of TNCs, their functioning and interactions with individual countries, as well as the impact of new technologies, in particular, artificial intelligence on corporate activities.